Wyrażenia kwantyfikujące i negacja w hebrajszczyźnie biblijnej - Termińska, Kamilla (Forum Lingwistyczne, 2015)
Quantifying expressions and negation in the Biblical Hebrew The article discusses Biblical Hebrew realizations of classical quantifiers, general and existential ones, both in assertive sentences and in combination with negation. Particular attention is paid to various quantifying expressions concerning the man and time, whose interpretation depends on a given field of interpretation. The problem of formula emphasizing and category illogicality of the expression ‘everything apart from’ has been highlighted and the major differences between the realizations of quantifier formulas in classical Hebrew and contemporary Polish have been outlined. Key words: general quantifier, existential quantifier, negation with a quantifier, field of interpretation, emphasis, idiomaticity of the ethnic language